Correction: Comparative Study of Dermal Pharmacokinetics Between Topical Drugs Using Open Flow Microperfusion in a Pig Model - Manfred Bodenlenz; Thean Yeoh; Gabriel Berstein; Shibin Mathew; Jaymin Shah; Christopher Banfield; Brett Hollingshead; Stefanus J. Steyn; Sarah M. Osgood; Kevin Beaumont; Sonja Kainz; Christian Holeček; et al. (Pharmaceutical Research, 2024)

Comparative Study of Dermal Pharmacokinetics Between Topical Drugs Using Open Flow Microperfusion in a Pig Model - Manfred Bodenlenz; Thean Yeoh; Gabriel Berstein; Shibin Mathew; Jaymin Shah; Christopher Banfield; Brett Hollingshead; Stefanus J. Steyn; Sarah M. Osgood; Kevin Beaumont; Sonja Kainz; Christian Holeček; et al. (Pharmaceutical Research, 2024)
Purpose Accurate methods to determine dermal pharmacokinetics are important to increase the rate of clinical success in topical drug development. We investigated in an in vivo pig model whether the unbound drug concentration in the interstitial fluid as determined by dermal open flow microperfusion (dOFM) is a more reliable measure of dermal exposure compared to dermal biopsies for seven prescription or investigational drugs. In addition, we verified standard dOFM measurement using a recirculation approach and compared dosing frequencies (QD versus BID) and dose strengths (high versus low drug concentrations). Methods Domestic pigs were topically administered seven different drugs twice daily in two studies. On day 7, drug exposures in the dermis were assessed in two ways: (1) dOFM provided the total and unbound drug concentrations in dermal interstitial fluid, and (2) clean punch biopsies after heat separation provided the total concentrations in the upper and lower dermis. Results dOFM showed sufficient intra-study precision to distinguish interstitial fluid concentrations between different drugs, dose frequencies and dose strengths, and had good reproducibility between studies. Biopsy concentrations showed much higher and more variable values. Standard dOFM measurements were consistent with values obtained with the recirculation approach. Conclusions dOFM pig model is a robust and reproducible method to directly determine topical drug concentration in dermal interstitial fluid. Dermal biopsies were a less reliable measure of dermal exposure due to possible contributions from drug bound to tissue and drug associated with skin appendages.